2010
DOI: 10.1175/2010jpo4261.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mesoscale Eddies on Subduction and Distribution of Subtropical Mode Water in an Eddy-Resolving OGCM of the Western North Pacific

Abstract: The effects of mesoscale eddies on the subduction and distribution of the North Pacific Subtropical Mode Water (STMW) are investigated using an eddy-resolving ocean general circulation model (OGCM). First, the subduction rate is calculated and the contribution of eddies to the subduction of STMW is estimated. It is found that eddy subduction significantly contributes to the total subduction of STMW. Second, eddy thickness transport and diapycnal flux are directly diagnosed to investigate the large-scale eddy-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 49 publications
7
93
0
Order By: Relevance
“…For example, the eddy field can influence water mass transformation by contributing to the total subduction and ventilation rates (e.g. Gebbie, 2007;Nishikawa et al, 2010;Lachkar et al, 2009). Also, eddies are key in balancing the heat budget in the overflow regions and the deep convection sites (e.g.…”
Section: Motivationmentioning
confidence: 99%
“…For example, the eddy field can influence water mass transformation by contributing to the total subduction and ventilation rates (e.g. Gebbie, 2007;Nishikawa et al, 2010;Lachkar et al, 2009). Also, eddies are key in balancing the heat budget in the overflow regions and the deep convection sites (e.g.…”
Section: Motivationmentioning
confidence: 99%
“…The effects of mesoscale eddies on mode water formation have received increasing attention over the past decade due to the concurrent increase of remotely sensed and in situ observations [Uehara et al, 2003;Qiu and Chen, 2006;Qiu et al, 2007;Oka et al, 2009], and finer resolution OGCMs which resolve these processes [Qu et al, 2002;Nishikawa et al, 2010;Oka and Qiu, 2012]. Marshall [1997] suggested that in strong frontal regions where intense baroclinic instability occurs (e.g., in the Kuroshio Extension region), an ensemble of eddies provides advection via the ''bolus velocity.''…”
Section: Introductionmentioning
confidence: 99%
“…Using the output of a global high-resolution OGCM, Qu et al [2002] pointed out that mesoscale eddies enhance the annual subduction rate of North Pacific subtropical mode water (STMW) and central mode water (CMW) by up to 100 m/yr, or 34% of the total subduction. Recently, Nishikawa et al [2010] estimated that eddies contribute some 50% of the total mode water subduction rate based on an eddy-resolving OGCM (1/12 3 1/18 ) simulation of the western North Pacific. From a climatological viewpoint, subduction is limited to the intersections of the winter mixed layer depth (MLD) front and outcrop lines [Xie et al, 2000], but eddies may broaden the horizontal extent of the subduction sites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, spatial and temporal variability of the surface mixed layer depth (MLD) and water masses is one of the important metrics for assessing the reproduction of the surface layer variability (e.g., Toyoda et al 2015a). In addition, it has been indicated that smaller scale (eddy) processes are essential for the reproduction of MLD and surface-intermediate water masses (e.g., Ishizaki and Ishikawa 2004;Tsujino and Yasuda 2004;Nishikawa et al 2010). Thus, the present product (FORA-WNP30) is expected to effectively reproduce the MLD-water mass variability by adopting a high-resolution OGCM.…”
Section: Mixed Layer Depth and Water Mass Propertiesmentioning
confidence: 91%